HAK PREROGATIF PRESIDEN DALAM PENGANGKATAN DAN PEMBERHENTIAN KEPALA KEPOLISIAN NEGARA REPUBLIK INDONESIA BERDASARKAN UUD 1945 - Kaharudin, Kaharudin; Galang Asmara, HM; Minollah, Minollah; Jayadi, Haeruman (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2016)
The research was intended to determine the prerogative of the President on the Constitution of the Republic of Indonesia 1945, and to know the prerogative of the President in the appointment and dismissal of the Head of the Indonesian National Police, so as to prevent conflicts between the president and parliament in the appointment and dismissal of the police chief. The research method used is normative law research method with the statute approach and the conceptual approach. Through statute approach, researchers will conduct in-depth study of the article of the Constitution of the Republic of Indonesia 1945, and the Act on the prerogative of the President in the appointment and dismissal of the police chief. While the conceptual approach, researchers will study the concepts of the thinking of experts in Constitutional Law related to the prerogative of the President in the appointment and dismissal of the police chief. The results showed that the prerogative of the President in the appointment and dismissal of the Chief of Police is restricted by the requirement for approval of the House of Representatives as a form of checks and balances between state institutions. This is a form of control of the House of Representatives as a representative of all the people of Indonesia who have sovereignty under the Constitution of 1945.